Assessment of Groundwater Response Scenarios for Surrounding Areas After Filling the Proposed Badush Dam Reservoir, Northern Iraq - Maha Shaher Badowi; Sabbar Abdullah Saleh; Mohammad Rashid Abood (Tikrit Journal of Pure Science, 2023)
In the current study, the depth of groundwater was detected in (39) wells in the banks surrounding Tigris River between Mosul and Badush dams, and then the maps of depth and level of groundwater were drawn. To predict the response of groundwater behavior in the banks of Badush reservoir in the strips adjacent to the river when starting the filling process, the lines of selected water levels in Badush dam were plotted on the map of groundwater equipotential lines to detect the areas confined between the water level in the reservoir and the same level for groundwater. It is assumed that these areas are affected by the bank storage; therefore, they are prone to leakage or geotechnical problems within the zone of engineering facilities foundations including Badush Dam itself, the regulatory dam and infrastructure projects. In the pre-storage stage, it is noted that the area of influence of the bank storage is very limited and does not exceed 2 km2 on each side of the river in the area very close to the dam. When the water level raises more at the beginning of the storage, the area of influence of the bank storage will extend towards the upstream close to the river meandering. The effect on the eastern bank (left) will be wider compared to the situation in the western bank (right) where the effect is limited. The eastern side is characterized by having a higher population density and more urban establishments; therefore, the foundations of these establishments will be more affected. The area affected by the bank storage continues to widen towards upstream with the increase in the level of the dam reservoir until the effect reaches the maximum limit and approaches the shoulders of the regulatory dam, when the water levels in Badush reservoir are more than 245 m above sea level (a. s. l.). The variation in the groundwater extension effect with the continuous or gradual filling of reservoir requires monitoring and caution during filling, for fear of affecting the geotechnical properties of the soil and rocks within the foundations zone, and thus affecting the stability of the two dams.